Functional hepatic deterioration determined by 13C-methacetin breath test is associated with impaired hemodynamics and late Fontan failure in adults - Schleiger, Anastasia; Kramer, Peter; Sallmon, Hannes; Jentsch, Niklas; Pileckaite, Marta; Danne, Friederike; Schafstedde, Marie; Müller, Hans-Peter; Müller, Tobias; Tacke, Frank; Jara, Maximilian; Stockmann, Martin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Despite improved survival a substantial number of Fontan patients eventually develop late failure. Fontan-associated liver disease (FALD) is one of the most common end-organ dysfunctions. Although impaired hemodynamics and Fontan failure correlate with FALD severity, no association between hepatic functional metabolic impairment and Fontan hemodynamics has been established. Hypothesis: Enzymatic liver function measured by liver maximum function capacity test (LiMAx®) correlates with Fontan hemodynamics and Fontan failure. Methods: From 2020 to 2022, 51 adult Fontan patients (mean age: 28.5±6.7 years, mean follow-up time after Fontan operation: 23.3±6.8 years) were analyzed in a cross-sectional study. Hemodynamic assessment included echocardiography, cardiopulmonary exercise testing and invasive hemodynamic evaluation. Fontan failure was defined based on our recently composed multimodal Fontan failure score. Results: Maximum liver function capacity as assessed by LiMAx® test was normal in 36 patients (>315 µg/h*kg) and mildly to moderately impaired in 15 patients (140-314 µg/h*kg), while no patient displayed severe hepatic impairment (≤139 µg/kg*h). Fontan failure was present in 12 patients. Enzymatic liver function was significantly reduced in patients with increased pulmonary artery pressure (p=0.017) and ventricular end-diastolic pressure (p=0.017), respectively. In addition, maximum liver function capacity was significantly impaired in patients with late Fontan failure (289.0±99.6 µg/kg*h vs. 384.5±128.6 µg/kg*h, p=0.008). Conclusion: Maximum liver function capacity as determined by LiMAx® was significantly reduced in patients with late Fontan failure. In addition, elevated pulmonary artery pressure and end-diastolic ventricular pressure were associated with hepatic functional metabolic impairment.